The Process of Formulating Legislation - Loly Anggita Saragih (Warmadewa Press, 2024)
The development of national law in Indonesia is influenced upon the preparation of legislation, which is contingent upon the implementation of effective methods that bound all authorised institutions in the lawmaking process. The purpose of this study is to examine the underlying principles involved in the formulation of law in Indonesia, as well as the issues and barriers that arise during implementation. The primary goal of this research is to determine how far the current lawmaking process adheres to the principles of the rule of law in Pancasila, the protection of human rights, the principle of equality before the law, and the established principles of lawmaking outlined in applicable laws. This research also asks for to determine the extent to which a legal system that is just transparent, and responsive to society's needs can be formed through the legislative process, which is conducted by legitimate institutions that are selected through democratic processes. This paper investigates how Indonesia's legislative machinery might be improved to provide legal certainty and democratic government using normative and historical perspectives. This study is projected to improve the lawmaking process in Indonesia, promoting the creation of planned, integrated, and sustainable national law